Dimensi Pengungkapan Integrated Report dalam Menentukan Biaya Modal Ekuitas dengan External Financing Needs sebagai Variabel Moderasi - Filqy Nur Lailiyah; Ika Permatasari (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
The purpose of this study is to examine the extent to which the breadth of integrated report (IR) disclosure influences the cost of equity capital, as well as the role of external financing needs (EFN) as a moderating variable. This research analyzes data from companies included in the ESG index. The findings indicate that the level of integrated reporting (IR) disclosure does not have a significant impact on the magnitude of the company’s cost of equity capital. This suggests that merely increasing the quantity of information in the report is insufficient to reduce investors’ risk perception if the quality and clarity of the information do not reflect the company’s fundamental conditions. Conversely, EFN has been proven to significantly moderate this relationship. This implies that a credible funding structure can serve as a signal of financial discipline that enhances investor confidence. This study underscores the importance of considering a company’s financial condition when assessing the effectiveness of IR as a tool for communicating information to the capital market.